Factors Influencing Hospital Cleaners’ Knowledge and Practices toward Hepatitis B prevention in Northern Province of Rwanda - Jean Marie Vianney Nkurikiyintwali; Fidele Nizeyimana; Rosemary Okova; Erigene Rutayisire (Journal of Public Health International, 2021)
This study aimed to assess factors influencing knowledge and practices of hospital cleaners towards hepatitis B prevention. This was a hospital-based cross-sectional study conducted at in Northern Province of Rwanda. A pretested self-administered questionnaire was used to gather data from study participants. A total of 134 cleaners were recruited in the study. Data were entered using Kobo collect toolbox and exported to Microsoft office excel for data cleaning and to entered in SPSS version 21 for analysis. Descriptive and logistic regression analysis was done and the significance level was 5%. More than a half of respondents were female (51.5%), and had primary level of education (54.5%). Results showed that only 9.7% of respondents had a high level of knowledge about HBV and only 2.2% had good practices on HBV practices. The odds of having high level of knowledge towards HBV prevention was 2.3 times (AOR=2.3, 95%CI: (1.1-27.3); p=0.045) among respondents with high school compared to those with no educational level. Respondents with work experience of 5-7 years were 1.5 times to have high level of knowledge towards HBV prevention than those with work experience of less than one year. Being aged between 20-30 years was associated with 2.5 times more likely to have good practices on HBV prevention than respondents aged less than 20 years. The odds of having good practice towards HBV had found to increase with work experience (AOR=2.3; 95%CI: (1.29-4.3); p=0.014). Considerable proportion of participants lacks the requisite knowledge of post-exposure treatment and prevention of HBV. Training programs on HBV infection, including PEP are highly recommended.
Keywords: Hepatitis B